Pengaruh Model Pembelajaran Case Based Learnıng (Cbl) Terhadap Kemampuan Lıterası Saıns Ipa Sıswa Kelas V - lina faiza; fitria Wulandari (Elementary Teacher Education Program, Majalengka University, 2023)
This study aims to determine whether there is an influence of the Case Based Learning (CBL) learning model on the science literacy skills of fifth grade students at SD Muhammadiyah 1 Krian. The research method used is the experimental method with the research design, namely the pre-experimental design and the type of research, namely the One Group Pretest-Posttest design. Data on the results of students' reasoning abilities were obtained through tests of essay questions before and after using the CBL learning model. The research results were analyzed using the N-Gain test with the help of SPSS software and Microsoft Excel. The results of the analysis using the N-Gain test obtained an average result of 0.47 which is included in the medium category. This shows that the CBL learning model can have a moderate effect on students' reasoning abilities.